Health anxiety and hypochondriasis in the light of DSM-5. Issue 2 (3rd March 2016) - Bailer, Josef; Kerstner, Tobias; Witthöft, Michael; Diener, Carsten; Mier, Daniela; Rist, Fred
Abstract : Background: In the DSM-5, the diagnosis of hypochondriasis was replaced by two new diagnositic entities: somatic symptom disorder (SSD) and illness anxiety disorder (IAD). Both diagnoses share high health anxiety as a common criterion, but additonal somatic symptoms are only required for SSD but not IAD.Design: Our aim was to provide empirical evidence for the validity of these new diagnoses using data from a case–control study of highly health-anxious ( n = 96), depressed ( n = 52), and healthy ( n = 52) individuals.Results: The individuals originally diagnosed as DSM-IV hypochondriasis predominantly met criteria for SSD (74%) and rarely for IAD (26%). Individuals with SSD were more impaired, had more often comorbid panic and generalized anxiety disorders, and had more medical consultations as those with IAD. Yet, no significant differences were found between SSD and IAD with regard to levels of health anxiety, other hypochondriacial characteristics, illness behavior, somatic symptom attributions, and physical concerns, whereas both groups differed significantly from clinical and healthy controls in all of these variables.Conclusion: These results do not support the proposed splitting of health anxiety/hypochondriasis into two diagnoses. Further validation studies with larger samples and additional control groups are warranted to prove the validity of the new diagnoses.